canonical pathway for selenocysteine insertion is dispensable in Trypanosomes - Aeby, Eric; Palioura, Sotiria; Pusnik, Mascha; Marazzi, Janine; Lieberman, Allyson; Ullu, Elisabetta; Söll, Dieter; Schneider, André (Proceedings of the National Academy of Sciences - PNAS, 2009)
The micronutrient selenium is found in proteins as selenocysteine (Sec), the 21st amino acid cotranslationally inserted in response to a UGA codon. In vitro studies in archaea and mouse showed that Sec-tRNASec formation is a 3-step process starting with serylation of tRNASec by seryl-tRNA synthetase (SerRS), phosphorylation of serine to form phosphoserine (Sep)-tRNASec by phosphoseryl-tRNASec kinase (PSTK), and conversion to Sec-tRNASec by Sep-tRNA:Sec-tRNA synthase (SepSecS). However, a complete study of eukaryotic selenoprotein synthesis has been lacking. Here, we present an analysis of Sec-tRNASec formation in the parasitic protozoon Trypanosoma brucei in vivo. Null mutants of either PSTK or SepSecS abolished selenoprotein synthesis, demonstrating the essentiality of both enzymes for Sec-tRNASec formation. Growth of the 2 knockout strains was not impaired; thus, unlike mammals, trypanosomes do not require selenoproteins for viability. Analysis of conditional RNAi strains showed that SerRS, selenophosphate synthase, and the Sec-specific elongation factor, EFSec, are also essential for selenoprotein synthesis. These results with T. brucei imply that eukaryotes have a single pathway of Sec-tRNASec synthesis that requires Sep-tRNASec as an intermediate.